Cochrane Database of Systematic Reviews 2013
DOI: 10.1002/14651858.cd006965.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of restricted caffeine intake by mother on fetal, neonatal and pregnancy outcome

Abstract: There is insufficient evidence to confirm or refute the effectiveness of caffeine avoidance on birthweight or other pregnancy outcomes. There is a need to conduct high-quality, double-blinded RCTs to determine whether caffeine has any effect on pregnancy outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…En cuanto al consumo de substancias lícitas durante el embarazo, los datos de prevalencia del consumo de cafeína en la literatura son muy limitados a pesar de ser la substancia psicoactiva más ampliamente consumida en el mundo (Kuczkowski, 2009). En nuestra muestra, un 40% de las mujeres embarazadas tomaban de media 1-2 tazas de café al día, acercándose a los niveles descritos de cafeína (> 200mg/dia) que se asocian con efectos negativos sobre el embarazo y el periodo perinatal (Chen, Bell, Browne, Druschel y Romitti, 2014;Modzelewska et al, 2019), recomendándose reducir la ingesta de cafeína al mínimo durante el embarazo (Jahanfar y Jaafar, 2013).…”
Section: Prevalencia De Consumo De Sustancias Legales E Ilegales Duraunclassified
“…En cuanto al consumo de substancias lícitas durante el embarazo, los datos de prevalencia del consumo de cafeína en la literatura son muy limitados a pesar de ser la substancia psicoactiva más ampliamente consumida en el mundo (Kuczkowski, 2009). En nuestra muestra, un 40% de las mujeres embarazadas tomaban de media 1-2 tazas de café al día, acercándose a los niveles descritos de cafeína (> 200mg/dia) que se asocian con efectos negativos sobre el embarazo y el periodo perinatal (Chen, Bell, Browne, Druschel y Romitti, 2014;Modzelewska et al, 2019), recomendándose reducir la ingesta de cafeína al mínimo durante el embarazo (Jahanfar y Jaafar, 2013).…”
Section: Prevalencia De Consumo De Sustancias Legales E Ilegales Duraunclassified
“…On the other hand, doses of caffeine under approximately 200 mga day can be considered harmless in pregnancy. Jahanfar and Jaafar demonstrated that a dose of caffeine 182 mg per a day had no effect on birthweight or length of gestation (96).…”
Section: Caffeine Toxicitymentioning
confidence: 99%
“…fetal alcohol syndrome) [56]. The consumption of caffeinated beverages should be in moderate amounts; not more than 3 cups of coffee per day [57].…”
Section: General Dietary Recommendations During Pregnancymentioning
confidence: 99%